Development of a Beginner Level Flexibility Training Model in Learning Archery - Susanto, Ratno; Fafa, M. Nur; Afandi, Achmad; Wahyuni, Luluk Indah Nur (Universitas Hamzanwadi, 2024)
This research produces archery training products, with various models with flexibility training. Archery is a sport of fine and gross motor skills, where success is determined by the capacity to shoot a target repeatedly with extraordinary precision and accuracy. One effort to get talented archery athletes is to conduct talent scouting from an early age. The program for scouting and developing talented athletes in developed countries whose achievements have been implemented with the support of adequate resources, including from government funds, the community, as well as expert support through cross- and inter-disciplinary scientific approaches. Flexibility shows the extent of movement in the joints. Only with sufficient flexibility can a person carry out a movement task with adequate performance. Because flexibility is an important element of physical fitness which is related to health and also physical fitness which is related to performance (achievement). The aim of this development is that the training model book in this research is to produce training media in the form of a flexibility model pocket book for interactive beginner students on basic theoretical competency material. Theoretical feasibility is seen from the feasibility of the material and the feasibility of the media. This research method uses ten stages of development to dissemination. The average percentage of material feasibility is 91% in the very feasible category, and the average percentage of media feasibility is 85.4% in the very feasible category. This archery technique training model book with flexibility is very suitable for use as training material. In terms of material content, this exercise book is very suitable because all the material contained in it is in accordance with basic competencies. Meanwhile, in terms of media suitability, this pocket book is also very suitable because the learning media used is suitable for the material and learning objectives to be achieved.